Analisis Fikih Lingkungan Mengenai Tindak Pidana Dalam Pasal 68 Huruf (A) UU No. 17 Tahun 2019 Tentang Sumber Daya Air - Baihaqi, Achmad (El-Dusturie, 2022)
The public interest is very oriented to the benefit and refuses damage to the community, nation and state from environmental damage, especially water which is very important for people's lives. 17 of 2019 which states "every person who intentionally carries out activities that result in damage to water sources and infrastructure and/or water pollution as referred to in Article 25 letters b and d; or carrying out activities that result in the occurrence of Water Destructive Power as referred to in Article 36, shall be punished with imprisonment for a minimum of 3 (three) years and a maximum of 9 (nine) years and a fine of at least Rp. 5,000,000,000.00 (five billion rupiahs). ) and a maximum of Rp. 15,000,000,000.00 (fifteen billion rupiah).According to Islamic law, it can be implemented because according to the author it is very in line with the objectives of Islamic law (Maqosid Al Shari'ah), because it maintains five things in human interests to maintain religion, preserve the soul, maintain offspring, maintain reason, and maintain property. Even the perpetrators can be sentenced to a maximum sentence (imprisonment and fines) if they are really guilty in accordance with the applicable principles of justice.Kepentingan umum berorientasikan pada kemaslahatan dan menolak kerusakan. Contohnya air, dimana ia penting bagi kehidupan masyarakat. Sanksi pidana pasal 68 huruf a UU No. 17 tahun 2019 menyatakan “ setiap orang yang dengan sengaja melakukan kegiatan yang mengakibatkan kerusakan Sumber Air dan prasarananya dan/atau pencemaran Air sebagaimana dimaksud dalam Pasal 25 huruf b dan huruf d; atau melakukan kegiatan yang mengakibatkan terjadinya Daya Rusak Air sebagaimana dimaksud dalam Pasal 36 ”˜’ dipidana dengan pidana penjara paling singkat 3 (tiga) tahun dan paling lama 9 (sembilan) tahun dan denda paling sedikit Rp5.000.000.000,00 (lima miliar rupiah) dan paling banyak Rp15.000.000.000,00 (lima belas miliar rupiah).Menurut Hukum Islam dapat dilaksanakan karena menurut penulis sangat sesuai dengan tujuan Hukum Islam (Maqosid Al Syari’ah), karena menjaga lima hal kepentingan manusia untuk memelihara agama, memelihara jiwa, memelihara keturunan, memelihara akal, memelihara harta. Bahkan pelakunya dapat dijatuhi hukuman maksimal (penjara dan denda) bila betul-betul bersalah sesuai dengan asas keadilan yang berlaku.